Subclavian artery stenosis and subclavian steal syndrome - Manev N; Bushljetikj O; Petrovski Zh; Spiroski I; Kitanoski D; Zimbakov, Zh (My University, 2022)
Introduction- Atherosclerosis is the most common cause for subclavian artery stenosis. Other etiologies include Takayashi arteritis, thoracic outlet syndrome, compression syndromes, fibromuscular dysplasia and iatrogenic injury. It is estimated that approximately 2% of the population has subclavian artery stenosis, with a predominance of the left a.subclavia. Case report ----A 63 year old patient , with back pain, arm claudication and muscle fatigue, dizzines during working with left arm and tinnitus. Physical examination findings showed diference in both arm and blood pressures-sistolic( 50mmHg) and diastolic (20mmHg), coldness in left arm, diminishedradial pulsations. Arterial color Doppler , coronarography aortography and peripheral angiography were performed. Arterial Color Doppler showed transient systolic retrograde flow and anterograde diastolic flow through a.vertebralis, increased PSV> 340 ms and PSVr>3,0. Coronary finding -intermediate stenosis of the distal part of the right coronary artery. On aortography was seen critical ostial stenosis of the left a. subclavia between 95-99%. Peripheral angiogram of lower limb arteries showed genarilised atheromatosis. The threatment include ballon angioplasty and stentintg to a.subclavia Discussion - Subclavian steal should be considered among patient 50-70 year old , exhibiting vertebrobasilar territory neurological symptoms during arm activity. Blood presure measurement on both arm should be mandatory in patients with that symptomatology. Doppler ultrasound is the first step in differential diagnosis of arteria subclavia stenosis and it is usually confirmed with Ct arteriography and peripheral angiography of the aorta and upper limb. endovascular treatment with antegrade approach is the first choice of treatment in our institution, with high technical succes and safety. Conclusion- Endovascular treatment of a. subclavia stenosis should be consider as a therapeutic modality in all symptomatic patients. It characterizes with high blood procedure succes and excellent long term patency of the stent.
Keywords: subclavian stenosis; steal syndrome